Boro and Salt: materiality, substance and transformation in altoandin community families - Felipe Mario Zapata-Delgado (2019)
This research seeks to unravel as the families of Andean shepherds of the Arequipa region (Salinas Huito, Moche and Santa Lucia) have always had a subsistence economy based on the extraction of salt and grazing. In this context enter the mining Inkabor that through collective agreements with the communities the company requires labor; then the family living domestic production, exchange and consumption of salt, and grazing cattle, becomes wage in times of the year (four months) which is called the "campaign". Then this study attempts a rapprochement of their support system, production, circulation and consumption are transformed from the materialization of the salt and removal of boron, which implies new representations, the construction of a new rurality that has new symbolic meanings livelihood and culture, redefined as a subject within the current consumerist diversity.